Stories of dinosaurs - Punter, Russell (London : Usborne Publishing Ltd, 2007)
Make way for these dynamic dinosaurs- Kevin Kritosaurus faces a mighty megalosaur in a prehistoric wrestling match. The Raptor brothers have one hour to save their dino dinner from disaster. and a newborn hadrosaur goes on the rampage.
Shelving Location Readers Section. Fiction Book Section
Keywords: Children's fiction